Lead acid battery recycling for the twenty-first century - Ballantyne,AD; Hallett,JP; Riley,DJ; Shah,N; Payne,DJ (Royal Society Open Science, 2018)
There is a growing need to develop novel processes to recover lead from end-of-life lead-acid batteries, due to increasing energy costs of pyrometallurgical lead recovery, the resulting CO2 emissions and the catastrophic health implications of lead exposure from lead-to-air emissions. To address these issues, we are developing an iono-metallurgical process, aiming to displace the pyrometallurgical process that has dominated lead production for millennia. The proposed process involves the dissolution of Pb salts into the deep eutectic solvent (DES) Ethaline 200, a liquid formed when a 1 : 2 molar ratio of choline chloride and ethylene glycol are mixed together. Once dissolved, the Pb can be recovered through electrodeposition and the liquid can then be recycled for further Pb recycling. Firstly, DESs are being used to dissolve the lead compounds (PbCO3, PbO, PbO2 and PbSO4) involved and their solubilities measured by inductively coupled plasma optical emission spectrometry (ICP-OES). The resulting Pb2+ species are then reduced and electrodeposited as elemental lead at the cathode of an electrochemical cell; cyclic voltammetry and chronoamperometry are being used to determine the electrodeposition behaviour and mechanism. The electrodeposited films were characterized by scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). We discuss the implications and opportunities of such processes.